ANALISIS KONTRIBUSI SEKTOR INDUSTRI TERHADAP PDRB KOTA BATAM - Jurnal Ilmiah Manajemen Universitas Putera Batam (Universitas Putera Batam, 2018)
One indicator to see the economic growth of a region is to see the growth of Gross Regional Domestic Product (GRDP). GDP growth is dependent on the growth of several sectors of the economy, one of which is the industrial sector. Batam is the largest city in the Riau Islands whose economic base is the industrial sector. During the period of 2010 until 2016, the contribution of the industrial sector to Batam city gross domestic product tend to decrease. During the seven years only in 2013 which increased the contribution of industrial sector to PDRB Batam city. Because in 2013 the economic growth is relatively stable. During 2010-2016 the industrial production value always increased but its growth tended to decrease. The largest decrease occurred in 2016 that is decreased by 2.27% from (4.62-6.89). During the period 2010-2016 the contribution of the industrial sector to the GDP of Batam city is in very good category, this is because the contribution of this industry sector is always more than 50%.